2011
DOI: 10.1128/jvi.05445-11
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Entry Mediator and Nectin-1 Mediate Herpes Simplex Virus 1 Infection of the Murine Cornea

Abstract: Herpes simplex virus 1 (HSV-1) is a ubiquitous human pathogen that enters cells by the receptor-mediated fusion of the viral envelope with a host cell membrane. The envelope glycoprotein gD of HSV must bind to one of its receptors for entry to take place. Recent studies using knockout (KO) mice demonstrated that the gD receptors herpesvirus entry mediator (HVEM) and nectin-1 are the primary entry receptors for HSV-2 in the mouse vagina and brain. Nectin-1 was most crucial for the neuronal spread of HSV-2, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 33 publications
(40 reference statements)
5
65
1
Order By: Relevance
“…The very low infection efficiency might explain why double-KO mice were found to show no signs of infection with HSV (11)(12)(13). Since the 3-OS-HS generating 3-OST-3 enzyme (10) was detected in murine dermal fibroblasts, we suggest 3-OS-HS as a potential candidate to act as a rather inefficient receptor for HSV-1 on these cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The very low infection efficiency might explain why double-KO mice were found to show no signs of infection with HSV (11)(12)(13). Since the 3-OS-HS generating 3-OST-3 enzyme (10) was detected in murine dermal fibroblasts, we suggest 3-OS-HS as a potential candidate to act as a rather inefficient receptor for HSV-1 on these cells.…”
Section: Discussionmentioning
confidence: 93%
“…Since the absence of both nectin-1 and HVEM prevents HSV pathogenesis in the mouse model, nectin-1 and HVEM are reported to be the dominant functional gD receptors in the murine host (11)(12)(13). Using nectin-1-or HVEM-deficient mice, we recently investigated HSV-1 entry into murine epidermis.…”
mentioning
confidence: 99%
“…As noted above, prior studies using intravaginal or intracranial inoculation did not show any effect of knocking out HVEM on HSV-2 disease in mice (10,11). In an ocular scarification infection model using adult mice, Karaba et al demonstrated that disease due to HSV-1 was attenuated in the absence of HVEM expression (12). However, studies using HSV-2 in this model led to results which differ from those with HSV-1, showing no dependence of disease characteristics on HVEM expression (A. H. Karaba, S. J. Kopp, and R. Longnecker, submitted for publication).…”
Section: Discussionmentioning
confidence: 95%
“…Adult nectin-1 KO mice were resistant to encephalitis after direct intracerebral inoculation with HSV-2 (11). Interestingly, compared to that in WT mice, disease was attenuated in both HVEM KO and nectin-1 KO mice after corneal infection with HSV-1 (12).…”
mentioning
confidence: 96%
“…This method is clearly distinct from the natural entry route of HSV, but these studies helped us to understand pathogenesis. Expression of nectin-1 and HVEM was observed in the epithelium of the murine cornea (15,16), and infection studies with HSV-1 in KO mice indicated attenuated disease in the absence of either HVEM or nectin-1 (17). In contrast, HSV-2 does not require HVEM to cause disease in corneal infections, suggesting that the HVEM requirement depends on the serotype (18).…”
mentioning
confidence: 99%